2002
DOI: 10.1074/jbc.m104146200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Is an Important Factor Affecting the Membrane Insertion of β-Amyloid Peptide (Aβ1–40), Which May Potentially Inhibit the Fibril Formation

Abstract: ␤-Amyloid peptide (A␤), a normal constituent of neuronal and non-neuronal cells, has been proven to be the major component of extracellular plaque of Alzheimer's disease. Interactions between A␤ and neuronal membranes have been postulated to play an important role in the neuropathology of Alzheimer's disease. Here we show that A␤ is able to insert into lipid bilayer. The membrane insertion ability of A␤ is critically controlled by the ratio of cholesterol to phospholipids. In a low concentration of cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
158
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 55 publications
12
158
2
Order By: Relevance
“…5b). In fact, the concentration of cholesterol in the cytofacial leaflet of brain synaptic plasma membrane is lower in aged people (60), and A␤ cannot insert into the membrane containing less cholesterol (61). Once A␤ exits the membrane and enters into the extracellular solution, the segment of residues 29-40 has a high tendency to form short ␤-sheets (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5b). In fact, the concentration of cholesterol in the cytofacial leaflet of brain synaptic plasma membrane is lower in aged people (60), and A␤ cannot insert into the membrane containing less cholesterol (61). Once A␤ exits the membrane and enters into the extracellular solution, the segment of residues 29-40 has a high tendency to form short ␤-sheets (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been repeatedly reported that anionic phospholipids, such as phosphatidylserine, which becomes exposed in the outer membrane leaflet in apoptotic and tumoral cells, are putative docking sites for amyloid aggregates or can favor aggregate formation, thus initiating membrane impairment (38,50,51). Membrane cholesterol modulates membrane fluidity and may affect the incorporation of toxic aggregates into exposed cells (24,52) as well as membrane-associated Abeta fibrillogenesis and toxicity in neuronal cells (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted as described in our previous work (37). Lipids were dissolved in a solvent of chloroform/methanol (7:1 v/v, 1.0 mg/ml).…”
Section: Methodsmentioning
confidence: 99%